Orthodontic rubber band combined with magnetic ring as a traction device for improving endoscopic submucosal dissection training - Linfu Zheng; Longping Chen; Fuqiang Wang; Zhilin Liu; Xingjie Gao; Linxin Zhou; Kun Lin; Zaixia Wang; Baoxiang Luo; Dazhou Li; Wen Wang (BMC Medical Education)
Abstract Background Good exposure of the submucosal visual field is a prerequisite for successful endoscopic submucosal dissection (ESD). There are few reports on ESD training using orthodontic rubber band combined with magnetic ring traction (ORB-MR). This study evaluated the efficacy of ORB-MR traction for ESD training. Methods This study utilized an ex vivo porcine gastric model. Doctors experienced in endoscopic mucosal resection (> 100 cases), but not in ESD, were randomly divided into conventional and ORB-MR-assisted ESD groups. The practicality of ORB-MR traction was evaluated and procedure outcomes were compared between the two groups. The cumulative sum (CUSUM) method was used to construct the learning curves of ORB-MR and traditional ESD trainees respectively. Results A questionnaire survey of the ORB-MR-ESD group showed good satisfaction with ORB-MR. Per-Protocol analysis showed that the resection speed was faster in the ORB-MR group compared to the ESD group (11.61 ± 3.79 mm2/min vs. 6.66 ± 2.29 mm2/min, p < 0.001). Additionally, the former group exhibited a shorter operative time, lower submucosal injection volume, better visual field satisfaction, and a lower muscle injury rate. The learning curve of the ORB-MR physician reached the learning inflection point in case 9, while the learning inflection point of the traditional ESD physician appeared later, at case 13. Conclusions ORB-MR traction proved feasible and practical for ESD. It shortened the learning curve for ESD trainees and exhibited potential as a valuable method for ESD training.